1992
DOI: 10.1111/j.1365-2036.1992.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole in the long‐term treatment of severe gastro‐oesophageal reflux disease in patients with systemic sclerosis

Abstract: Twenty-five patients with systemic sclerosis and severe gastrooesophageal reflux disease were treated with 20-80 mg omeprazole daily for up to 5 years. Efficacy of treatment was assessed by symptom score, by endoscopic and histopathological surveillance of the oesophageal and gastric mucosa, and by laboratory screening including serum gastrin concentration.confirmed the efficacy of this treatment. However, complete healing of oesophagitis was not achieved in half of the patients due to residual gastro-oesophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 19 publications
1
33
1
Order By: Relevance
“…Hendel and colleagues reported that complete healing of oesophagitis was achieved in less than a half of patients with advanced SSc treated with omeprazole [27]. In contrast, we could show in our patients with early SSc that adequate PPI therapy and elimination of Hp led to complete mucosal healing in the distal oesophagus and stomach.…”
Section: Discussioncontrasting
confidence: 76%
“…Hendel and colleagues reported that complete healing of oesophagitis was achieved in less than a half of patients with advanced SSc treated with omeprazole [27]. In contrast, we could show in our patients with early SSc that adequate PPI therapy and elimination of Hp led to complete mucosal healing in the distal oesophagus and stomach.…”
Section: Discussioncontrasting
confidence: 76%
“…18 Even adding ranitidine at night to omeprazole does not improve nocturnal acid breakthrough and quality of life in these patients. 19 -Data from impedance studies show that treatment with acid reducing medications only affects acid production and raises the pH of the gastric refluxate, but reflux still occurs as the frequency and duration of reflux episodes is not affected.…”
Section: Connective Tissue Disorders and Esophageal Motilitymentioning
confidence: 99%
“…17 Therapeutic Implications Proton pump inhibitors have been the main form of treatment for GERD in patients with CTD, while surgery has been rarely considered. 18,19 This approach stems from the belief that peristalsis is absent in most patients with CTD so that a fundoplication must be avoided for fear of creating or worsening dysphagia. This mind-set has several pitfalls because of the following reasons:…”
Section: Connective Tissue Disorders and Esophageal Motilitymentioning
confidence: 99%
“…Based on the underlying esophageal motor dysfunction, gastroesophageal reflux with its potential complication is the most important clinical manifestation of gastrointestinal involvement in systemic sclerosis. Many patients require more intensive medical therapy to control symptoms and/or heal mucosal disease [31][32][33]. Generally, this treatment should rely on proton pump inhibitors as the most effective acid suppressive medication.…”
Section: Esophageal Manifestationsmentioning
confidence: 99%